Social Development Problems for the Kalaotoa Island Community, Selayar Islands Regency - Atira, Fatwa; Sulistiawati, Sulistiawati; Irwana, Dyah Khafifah; Jusnianti, Jusnianti; Sandriani, Andi (Formosa Journal of Applied Sciences, 2024)
The goal is to create purposeful individuals so they can live creative, healthy, and rewarding lives. So that everyone becomes more aware, responsible and able to participate in development, social development must be implemented. National development cannot be separated from the development of archipelagic regions. However, development must be accelerated considering the unique problems in archipelagic areas, such as the lack of laws that support island development, inadequate communication and infrastructure connecting large and small islands for economic activities, and inadequate management of natural resource empowerment. The development of island regions is expected to improve community welfare both directly and indirectly and close development gaps between regions.